PERAN AYAH DALAM PERSPEKTIF AL-QUR'AN: (Studi Tentang Kisah Luqman, Ibrahim, dan Syu'aib) - Moh Abdulloh Hilmi; Jannah, Roudhotul; Ulya, Vita Fitriatul (Prodi Ilmu Al-Qur'an dan Tafsir, 2023)
This article explores the representation of fathers' roles in the Qur'an, addressing a recent bias that narrowly sees them as providers, overlooking their crucial role as character builders for their children. The Qur'an illuminates the father's role through the stories of Luqman, Ibrahim, and Syu'aib, showcasing the multifaceted nature of their roles with a focus on two-way communication and interpersonal dynamics. Using a qualitative approach, specifically a literature study with a descriptive-analytical method, the analysis reveals a communication framework in the Qur'an's verses concerning fathers and their children. The Qur'an delineates the responsibilities fathers should uphold in nurturing their children's development. Additionally, the stories of Luqman, Ibrahim, and Syu'aib demonstrate unique and individualistic fatherly approaches, with the communication strategies employed positively impacting the psychological well-being of children.